The Representation of Character Education Values in the ELT Textbook for Junior High School Students - Reiva Presty Hasana; Sugeng Ariyanto; I Putu Sukmaantara (Institut Agama Islam Negeri Palopo, 2023)
In recent decades, character education in language education has been discussed and studied. Textbooks are an important role to channel certain character education values. The readers not only get knowledge about academic materials but also get good values represented in the book. ELT textbooks used in secondary schools are no exception. In response to this, this article reports on a critical discourse analysis study that examines how character education values according PPK program are represented in English textbooks published by the Indonesian Ministry of Education and Culture using qualitative research design. Semiotic analysis shows that ELT textbooks represent character education values presented in the form of visual artifacts. The findings conclude that visual artifacts in textbooks do not always depict character education values. Therefore, textbook writers and teachers need to consider the values when developing and using ELT textbooks.